Expression of the Annexin A1 and its correlation with matrix metalloproteinases and the receptor for formylated peptide-2 in diffuse astrocytic tumors - Tadei, Maryam Buainain; Mayorquim, Matheus Vicente; de Souza, Camila Brambilla; de Souza Costa, Sara; Possebon, Lucas [UNESP]; Souza, Helena Ribeiro; Iyomasa-Pilon, Melina Mizusaki; Geromel, Mairto Roberis; Girol, Ana Paula [UNESP] (Elsevier, 2018)
Astrocytomas represent the majority of cerebral gliomas. Studies show that the anti-inflammatory protein Annexin-A1 (ANXA1) is associated with the tumor invasion process and that its actions can be mediated by the receptor for formylated peptides (FPR). Therefore, we evaluated the expression of ANXA1, the receptor FPR2 and matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9) in brain astrocytomas. Detection of proteins was performed in sections of diffuse astrocytomas (grade II), anaplastic astrocytomas (grade III) and glioblastomas (GBM, grade IV) and quantifications were made by densitometry. Our analyses showed increased expression of ANXA1 in astrocytomas of all grades, but especially in GBM. The expression of FPR2 is similar to that found for ANXA1, being higher in GBM. Immunostaining for MMPs is also stronger as the degree of malignancy increases, especially with respect to MMP-9. The positive correlation between ANXA1/FPR2 and ANXA1/MMP-9 was observed in all tumors studied. The data indicate the possible action of ANXA1 and FPR2 on the development and progression of astrocytomas, related to increased expression of MMP-9. Thereby, ANXA1 and FPR2 are involved in the biology and malignancy of diffuse astrocytic tumors.
Keywords: Annexin A1; Astrocytomas; FPR; Glioblastomas; Metalloproteinases